Topography studies of concrete abraded with ice - Shamsutdinova, Guzel; Hendriks, Max; Jacobsen, Stefan (Wear, 2019)
Topography studies of concrete-ice abrasion were made to proceed in our understanding of the mechanisms of concrete wear by ice on Arctic offshore structures. The effects on various initial surfaces of a B75 normal-weight concrete (smooth, rough, sawn) and on the sawn surface of a LB60 lightweight concrete were studied during concrete-ice abrasion experiments. The degradation of a concrete surface appears mainly as valley formation resulting from air voids opening, or aggregate protrusion and cutting of peaks. The various initial roughness conditions were found to lead to an evolution with both increasing (at both meso- and microscale) and converging roughness. Protrusions from both lightweight and normal-weight aggregates were observed on sawn surfaces. Greater abrasion is seen on lightweight concrete and its initial roughness was much affected by the porous aggregate. acceptedVersion © 2019. This is the authors’ accepted and refereed manuscript to the article. Locked until 15 April 2021 due to copyright restrictions. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/